Comparison of the effectiveness of three different treatment methods for temporomandibular joint disc displacement without reduction. Issue 5 (May 2017) - Tatli, U.; Benlidayi, M.E.; Ekren, O.; Salimov, F.
Abstract: The aim of this study was to compare the effectiveness of three treatment methods for unilateral temporomandibular joint (TMJ) disc displacement without reduction (DDwoR). One hundred and twenty patients with unilateral TMJ DDwoR were assigned randomly to one of three treatment groups (40 patients in each): group 1 received arthrocentesis, group 2 received stabilization splint therapy following arthrocentesis, and group 3 received splint therapy only. The groups were compared in terms of pain (visual analogue scale), joint function (maximum mouth opening and laterotrusive movements), disability and psychological status (validated questionnaire), and success rates. These were recorded before treatment and during follow-up after treatment (1, 3, and 6 months). The between-group and within-group differences in the data were analyzed statistically. The baseline characteristics were similar in all groups ( P   >  0.05). Significant improvements were noted in all parameters compared to baseline values in all groups (all P <  0.01). Groups 1 and 2 showed comparable outcomes that were superior to those of group 3. Arthrocentesis reduces pain and functional impairment more rapidly and effectively than splint therapy. Simultaneous splint application has no additional effect on the effectiveness of arthrocentesis for the treatment of unilateral DDwoR.